Wizualność Google Search - Kopeć , Jarosław (Człowiek i Społeczeństwo, 2013)
The article discusses the issue of colour-related metaphors used by institutions and common users for describing the experience of using the Web. The context of thinking about modern Internet in this text is provided by William Gibson’s classic cyberpunk novel – Neuromancer. I assume that colours may be persuasive in presenting the Internet in specific, political and business-related context.